Assessment Techniques for Arabic Speaking Skills (Maharah Kalam) in Non-Formal Education: A Case Study of Aidina Ocean Classroom Course - Mhd Ibnu Hanan Al Faruqi; Surya Hidayat; Hadri Hadri; Moh Taufikurrahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe the evaluation techniques applied in Arabic learning activities on the aspect of speaking skills in the Aidina Ocean classroom. Evaluation is an important component of the language learning process because it functions as a tool to measure student achievement and evaluate the effectiveness of teaching methods. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of Aidina class teachers and active students. This research contributes to uncovering the evaluation techniques used in learning speech skills. Through a qualitative descriptive approach, the researcher describes in detail the form, process, and main contribution of this study is to present empirical data on non-formal evaluation practices that are rarely raised in the context of Arabic language courses outside formal educational institutions. The results of the study showed that the evaluation technique used had two stages of evaluation, namely evaluation activities in the classroom and outside the classroom. Evaluation in class is an oral exam from the book of Kalimatul Af'al Al Yaumiah and the book of Kalimatul Asma' Al-Yaumiyah which consists of daily evaluation, weekly evaluation and monthly evaluation. Meanwhile, outside the classroom, there was an Arabic drama performance and an evaluation with a psychological approach to students carried out by the supervisor dormitory companion.